How Can Digital Maps of Religions Inform Us about Fractionalization and Polarization in Post-Communist Romania? - Marina-Alexandra Rotaru; Remus Creţan; Ioan Sebastian Jucu; Ana-Neli Ianăş; Marcel Török-Oance (Religions, 2024)
This study explores religious diversity in Romania and how the trends of indices of religious fractionalization and polarization manifest at the county level in a post-communist period. The county level was selected as the relevant level for analysis due to its more clearly visible spatial dynamics with regard to religions. Recent studies have revealed that the erosion of diversity is an important aspect for any country and needs to be considered as an important aspect of democracy. This paper highlights how digital mapping of religious polarization and fractionalization in Romania has been generally maintained, although the regions of Transylvania, Banat, Dobrogea and Western Moldova remain areas in which there are different religions. Other than the general aspect of religious diversity depending on ethnic trends, there has been a rise of Pentecostals and Baptists at the county level. This aspect has further implications for our study, which calls for creating new institutions for dialogue between majority Orthodox communities and Protestants, not only so that potential conflicts do not appear between Orthodox and emerging religious communities but also to ensure objective, cultural, religious coherence. Our maps revealed the distribution patterns and the temporal evolution of religious denominations for the 1992–2011 period. The major line of originality in our research rests in the findings that after conducting a bivariate spatial autocorrelation analysis of religious fractionalization and polarization, we were able to identify two distinct clusters with spatial overlap over historical provinces.